EP 18. Deep Brain Stimulation improves behavior and modulates neural circuits in a rodent model of schizophrenia. Issue 9 (September 2016) - Hadar, R.; Bikovsky, L.; Soto-Montenegro, M.; Klein, J.; Weiner, I.; Pascau, J.; Hamani, C.; Winter, C.
Abstract : Background: A growing body of evidence suggests that schizophrenia (scz) is a neurodevelopmental disorder in which some brain alterations already occur during early brain development and others progress along the developmental course. This progressive nature of scz raises interest in the development of preventive avenues, i.e. therapeutic interventions prior to the full symptoms manifestation. For that however, a profounder understanding of the exact nature of altered brain development in scz is needed. Given methodological and ethical limitations of human studies, the use of appropriate animal models of schizophrenia is an invaluable tool. Methods: This study used a maternal immune stimulation (MIS) rodent model of schizophrenia together with a neuromodulation approach, namely deep brain stimulation (DBS), to investigate the neurobiological and behavioral alterations during the course of disease. In this model, the exposure of pregnant rodents on their gestational day 15 to the viral mimic polyriboinosinic-polyribocytidylic acid (poly I:C) results in schizophrenia-relevant behavioral abnormalities which first emerge in adulthood, complying with the postnatal delay of this disorder. We applied DBS-interventions to the medial prefrontal cortex (mPFC) or nucleus accumbens (Nacc) to either poly I:C progeny or controls, at two different time points of scz development: a continuous DBS during a pre-symptomatic adolescence period and an acute DBS at the full symptomatic period of adulthood. In adulthood, we tested the effects of both interventions on two behavioral processes known to be disrupted in scz and in this model: sensorimotor gating and attentional selectivity. In addition, we studied the effects of DBS on several neurobiological parameters at post mortem . Results: When applied at adulthood, DBS to both regions was found to be successful in alleviating sensorimotor gating and attentional selectivity deficits in the MIS model. However, when applied in adolescence only mPFC stimulation prevented both behavioral deficits, whereas Nacc stimulation only normalized sensorimotor deficits. Moreover, stimulation in those two brain sites induced different brain metabolic effects and neurochemical alterations, even if the effect on behavior was identical. Conclusions: This study adds to the growing literature suggesting that electrical stimulation of specific brain regions improves behavioral deficits in neuro-psychiatric disorders and also scz. Moreover, this study indicates that early neuro-modulation might halt the progression of scz in reliance on stimulation site.